Rotation Benefits From N2-Fixing Grain Legumes to Cereals: From Increases in Seed Yield and Quality to Greater Household Cash-Income by a Following Maize Crop - Lengwati, David M.; Mathews, Cherian; Dakora, Felix D. (Frontiers in Sustainable Food Systems, 2020)
We investigated Bambara groundnut, groundnut, mung bean, cowpea and black gram for use as biofertilizers in cropping systems. The 15N natural abundance technique was used to measure N2 fixation in this study. The percent N derived from fixation by mung bean (Vigna radiata L. Wilczek), Bambara groundnut (Vigna subterranea L. Verdc.), cowpea (Vigna unguiculata L.Walp.), black gram (Vigna mungo L.) and groundnut (Arachis hypogaea L was 98, 83, 79, 66 and 45% respectively. Nitrogen contribution by these legumes was 83, 67, 39, 36 and 32 kg.ha-1 respectively for Bambara groundnut, groundnut, mung bean, black gram and cowpea. Maize grain yield without N fertilizer was 2449, 2291, 2204, 2046 and 1671 kg.ha-1 respectively for maize following groundnut, Bambara groundnut, cowpea, mung bean, black gram and maize. Grain yield increase of maize after legumes without N fertilizer was 47, 46, 37, 32 and 22% respectively for groundnut, Bambara groundnut, cowpea, mung bean, and black gram. Supplying N0 up to N60 to maize plants increased shoot DM from 3264 to 4279 kg.ha-1, yield grain from 2184 to 3586 kg.ha-1, and whole-plant DM from 5448 to 7865 kg.ha-1, which represented 31, 64 and 44% increase with N fertilizer supply from 0 to 60 kg N ha-1. Symbiotic N benefit of preceding legumes to maize without N fertilizer was 20 to 40 kg N. ha-1 in fertilizer equivalents. The preceding legumes increased maize grain concentrations of P, Ca, S, Fe, Mn and Zn in zero-N plots relative to maize after maize. There was 225, 222, 180, 154 and 108% increase in marginal returns of maize after groundnut, Bambara groundnut, cowpea, mung bean and black gram respectively without N fertilizer.